2009
DOI: 10.1186/1748-717x-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of collimator leaf width and treatment technique on stereotactic radiosurgery and radiotherapy plans for intra- and extracranial lesions

Abstract: Background: This study evaluated the dosimetric impact of various treatment techniques as well as collimator leaf width (2.5 vs 5 mm) for three groups of tumors -spine tumors, brain tumors abutting the brainstem, and liver tumors. These lesions often present challenges in maximizing dose to target volumes without exceeding critical organ tolerance. Specifically, this study evaluated the dosimetric benefits of various techniques and collimator leaf sizes as a function of lesion size and shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 25 publications
4
68
0
Order By: Relevance
“…Appropriate devices for patient setup and immobilization.Appropriate devices for proper motion management.Computerized treatment verification system.Digital access to MRI and positron emission tomography (PET) image data.Capability to characterize and quantify internal anatomical changes with respiratory motion (for thoracic and abdominal SBRT services).Multimodality image fusion capability.Capability to calculate, display, and evaluate composite dose for patients who have received prior radiation therapy.Linac‐based treatment delivery system with appropriate mechanical accuracy, field‐aperture size, and resolution for small‐target conformality, and image‐guidance devices for target localization and verification including motion management technology relevant to the scope of SRS‐SBRT services to be offered 6, 7 …”
Section: Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate devices for patient setup and immobilization.Appropriate devices for proper motion management.Computerized treatment verification system.Digital access to MRI and positron emission tomography (PET) image data.Capability to characterize and quantify internal anatomical changes with respiratory motion (for thoracic and abdominal SBRT services).Multimodality image fusion capability.Capability to calculate, display, and evaluate composite dose for patients who have received prior radiation therapy.Linac‐based treatment delivery system with appropriate mechanical accuracy, field‐aperture size, and resolution for small‐target conformality, and image‐guidance devices for target localization and verification including motion management technology relevant to the scope of SRS‐SBRT services to be offered 6, 7 …”
Section: Resourcesmentioning
confidence: 99%
“…Linac‐based treatment delivery system with appropriate mechanical accuracy, field‐aperture size, and resolution for small‐target conformality, and image‐guidance devices for target localization and verification including motion management technology relevant to the scope of SRS‐SBRT services to be offered 6, 7…”
Section: Resourcesmentioning
confidence: 99%
“…The advantage of the smaller leaf width has been studied by several groups [1][2][3][4][5][6][7][8][9][10][11], but with mixed results. Kubo et al [7] were the first to assess the conformity of threedimensional (3D) conformal plans using 1.7, 3 and 10 mm leaf width MLC systems.…”
mentioning
confidence: 99%
“…Burmeister et al [2], on the other hand, reported no apparent clinically significant difference between the 5 and 10 mm MLC systems on 3 patients treated with intensity-modulated radiotherapy except for very small target volumes or those with concavities that are small with respect to the MLC leaf width. More recently, Wu et al [11], in a preliminary evaluation of the dosimetric impact of a 2.5 mm MLC over the 5 mm MLC for various treatment techniques and for a subset of five brain tumour cases abutting the brainstem, showed that the 2.5 mm leaf width MLC in combination with the intensity-modulated radiotherapy technique can yield dosimetric benefits to the treatment of small lesions in cases involving complex target/organ-at-risk geometry. The current study was designed to provide a more comprehensive assessment of the performance of the 2.5 mm leaf MLC system over the 5 mm leaf system for target volumes characteristic of intracranial SRS, and assess if potential gains realised may be clinically meaningful.…”
mentioning
confidence: 99%
“…They found a small dosimetric advantage of 2.5 mm leaf width MLC system over 5 mm MLC system in terms of dose conformation, normal tissue exposure, and a rapid dose falloff. Wu et al (20) evaluated 2.5 mm HDMLC versus 5 mm MMLC for three groups of tumor — spine, brain, and liver. They found that 2.5 mm finer leaf width in combination with IMRT could yield dosimetric benefits in radiosurgery and hypofractionated stereotactic radiotherapy (HSRT).…”
Section: Discussionmentioning
confidence: 99%